2013
DOI: 10.3329/jdnmch.v18i2.16021
|View full text |Cite
|
Sign up to set email alerts
|

One month Ramadan Fast Improves Lipid Profile Status of Bangladeshi Male Volunteers

Abstract: :To evaluate the effect of Ramadan fast on serum lipid profile status of men, the study was carried out in the National Mushroom Development and Extension Centre, Sobhanbag, Savar Dhaka in association with the Department of Pharmacy and Department of Biochemistry and Molecular Biology, Jahangirnagar University, Savar, Dhaka. The experiment was conducted before and after the Arabic month, Ramadan, when there occurs a change both in the pattern and timing of dietary intake. Findings of the study shows Ramadan fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…Our findings did not agree with the findings of Ziaee et al who observed decrease in HDL-C and increase in LDl-C at the end of Ramadan fast 30 . Our findings also agree with the findings of a similar study done on male volunteers in Bangladeshi population 31 . From this study, it can be said that fasting is beneficial so far lipid profile is concerned and may have some protective role against the development of atherosclerotic cardiovascular disease.…”
Section: Study Groupssupporting
confidence: 93%
“…Our findings did not agree with the findings of Ziaee et al who observed decrease in HDL-C and increase in LDl-C at the end of Ramadan fast 30 . Our findings also agree with the findings of a similar study done on male volunteers in Bangladeshi population 31 . From this study, it can be said that fasting is beneficial so far lipid profile is concerned and may have some protective role against the development of atherosclerotic cardiovascular disease.…”
Section: Study Groupssupporting
confidence: 93%